Plasma exchange treatment of a diabetic ketoacidosis child with hyperlipidemia to avoid pancreatitis: a case report - Huang, Shuyue; Song, Fuying; Gao, Kang; Song, Yi; Chen, Xiaobo (Frontiers in Pediatrics, 2024)
Type 1 diabetes mellitus (T1DM) is a metabolic disorder characterized by an absolute deficiency of insulin due to pancreatic failure. Diabetes ketoacidosis (DKA) has emerged as one of the most common complications of T1DM. Although exceedingly rare, the onset of T1DM with DKA may result in lipemia secondary to severe hypertriglyceridemia (HTG), accounting for several cases in the pediatric population. Along this line, plasma exchange treatment in children with DKA and severe hyperlipidemia has only been reported in several cases. In this case report, the diagnosis of an 11-year-old girl with diabetes ketoacidosis accompanied by severe HTG, along with subsequent plasma exchange treatment, was presented. Initially, the patient received initial management with crystalloid fluid bolus and intravenous insulin therapy. Despite rapid correction of acidosis, persistent HTG subsequently prompted the plasma exchange treatment. A total of three sessions were administered over two days, leading to a significant reduction in the triglyceride levels and resolution of corneal opacity, indicating successful therapeutic intervention.